2019
DOI: 10.1093/ckj/sfz092
|View full text |Cite
|
Sign up to set email alerts
|

The longitudinal relationship between patient-reported outcomes and clinical characteristics among patients with focal segmental glomerulosclerosis in the Nephrotic Syndrome Study Network

Abstract: Background Understanding the relationship between clinical and patient-reported outcomes (PROs) will help support clinical care and future clinical trial design of novel therapies for focal segmental glomerulosclerosis (FSGS). Methods FSGS patients ≥8 years of age enrolled in the Nephrotic Syndrome Study Network completed Patient-Reported Outcomes Measurement Information System PRO measures of health-related quality of life (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 22 publications
2
12
0
Order By: Relevance
“…In summary, the findings presented are consistent with previous research in FSGS, MCD, and nephrotic syndrome that has demonstrated that while generic HRQOL J o u r n a l P r e -p r o o f measures capture important aspects of HRQOL, and that PROs can sensitively capture some outcomes in this population, the generic measures do not adequately capture the unique disease specific aspects of FSGS/MCD 16,[34][35][36] . These findings support our hypothesis that HRQOL measures for individuals with FSGS/MCD should incorporate both disease specific and generic HRQOL concepts.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In summary, the findings presented are consistent with previous research in FSGS, MCD, and nephrotic syndrome that has demonstrated that while generic HRQOL J o u r n a l P r e -p r o o f measures capture important aspects of HRQOL, and that PROs can sensitively capture some outcomes in this population, the generic measures do not adequately capture the unique disease specific aspects of FSGS/MCD 16,[34][35][36] . These findings support our hypothesis that HRQOL measures for individuals with FSGS/MCD should incorporate both disease specific and generic HRQOL concepts.…”
Section: Discussionsupporting
confidence: 86%
“…In summary, the findings presented are consistent with previous research in FSGS, MCD, and nephrotic syndrome that has demonstrated that although generic HRQoL measures capture important aspects of HRQoL and that PROs can sensitively capture some outcomes in this population, the generic measures do not adequately capture the unique disease-specific aspects of FSGS/MCD. 16 , 33 , 34 , 35 These findings support our hypothesis that HRQoL measures for individuals with FSGS/MCD should incorporate both disease-specific and generic HRQoL concepts. Furthermore, the findings from this study suggest that the commonalities between HRQoL in FSGS and MCD, as well as the commonalities in HRQoL between adults and children, should allow for the development of an HRQoL PRO measure that can be used in children (aged ≥8 years) and adults, as well as in both disorders, and is appropriate for use supporting FDA-based labeling claims.…”
Section: Discussionsupporting
confidence: 65%
“…While the gene for ACE2 is on the X chromosome [ 30 ], studies of sex-based differences in kidney ACE2 expression and the relationships between ACE2 expression and kidney injury are limited. Accordingly, our goal was to study ACE2 expression in the NEPTUNE cohort [ 31 ] of FSGS and to compare relationships between ACE2 expression, clinical variables, and pathology in males and females.…”
Section: Discussionmentioning
confidence: 99%
“…We studied a well-characterized cohort of male and female subjects with FSGS [ 31 ]. We chose to study FSGS because clinical outcomes are dependent on sex: outcomes are better in females than males [ 23 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation